Effects of a superoxide dismutase mimetic on biomarkers of lung angiogenesis and alveolarization during hyperoxia with intermittent hypoxia - Chang, Michael (e-Century Publishing Corporation, 2013)
Extremely premature neonates requiring oxygen therapy develop an accumulation of reactive oxygen species (ROS), impaired alveolarization and dysmorphic pulmonary vasculature. Regulators of ROS (i.e. antioxidants), alveolarization (i.e. matrix metalloproteinases - MMPs) and microvascular maturation (i.e. vascular endothelial growth factor - VEGF) are altered in bronchopulmonary dysplasia (BPD). We tested the hypothesis that early treatment with MnTBAP, a superoxide dismutase mimetic and superoxide anion and peroxynitrite scavenger, alters lung biomarkers of angiogenesis and alveolarization during hyperoxia with intermittent hypoxia (IH) in neonatal rats. Neonatal rats were exposed to 50% O(2) with brief IH episodes (12% O(2)) from P0 to P14, or to room air (RA). On P0, P1 & P2, the pups received a daily IP injection of 1, 5, or 10 mg/kg MnTBAP, or saline. At P14, the pups were either euthanized, or allowed to recover in RA until P21. RA littermates were similarly treated. Lung VEGF, sVEGFR-1, MMP-2, MMP-9 and TIMP-1 were determined. Low-dose MnTBAP (1 mg/kg) prevented the increase in lung VEGF induced by intermittent hypoxia noted in the control group. This dose was also effective for decreasing MMP-9 and MMP-9/TIMP-1 ratio suggesting an anti-inflammatory effect for MnTBAP. IH decreased MMP-2 with no ameliorating effect by MnTBAP. Our data demonstrate that brief, repeated intermittent hypoxia during hyperoxia can alter biomarkers responsible for normal microvascular and alveolar development. In addition to prevention of hypoxic events, the use of antioxidants needs to be explored as a possible therapeutic intervention in neonates at risk for the development of oxidative lung injury.